PENGEMBANGAN MEDIA BANTU (MESIN DRILL) DALAM MENINGKATKAN KETERAMPILAN SMASH BOLA VOLLY - Indra Kasih; Deni Rahman Marpaung (Journal Physical Education, Health and Recreation, 2018)
This research is development research which is a process or steps to develop a new product or perfect existing product, which can be justified. This study uses a qualitative and quantitative approach and using the research & development (R & D) development research method with the development design chosen is referring to the development proposed by Borg and Gall. Based on the data obtained from the results of volleyball smash skills based on the pretest and posttest, it was found that the results of volleyball smash skills at the pretest were the lowest score of 4 and the highest score 11. Whereas in the Posttest, the results of volleyball smash ability were lowest scores 6 and the highest score The average score and standard deviation at Pretest are 6.71 and 1.91 respectively, while the Posttest is 9.46 and 1.60. Comparison of the Effectiveness of the Learning Model each learning indicator for the new model (after using a drill machine) is more effective than the old learning model (before using a drill machine). The average effectiveness of the preparation indicators for the old learning model is 60% and the new learning model is 85.71%. The average effectiveness of the implementation indicators in the old model learning is 50% and the learning model is new 70%. The average effectiveness of the follow-up indicators for the old learning model is 57.86% and the learning of the new model is 80.71%. Total learning outcomes (average of all indicators) obtained also increased from 55.59% to 78.81%. So that it can be concluded that learning a new model (after using a drill machine) is more effective than the old learning model (before using a drill machine).